Highly Efficient Curtius Rearrangement Approach for the Synthesis of Unsymmetrical Sulfonimidoyl Ureas. Issue 7 (1st June 2017) - Zhou, Hao; Hong, Jianquan; Huang, Jiapian; Chen, Zhiyuan
Abstract: A highly efficient synthesis of unsymmetrical sulfoximine ureas is developed. The reaction unites simple N H‐sulfoximines and acyl azides by a formal Curtius rearrangement as the key step. This reaction could be easily scaled up to gram scale and omits the generation of hazardous byproducts, thus allowing a practical and environmentally benign path for the synthesis of medicinally important sulfonimidoyl unsymmetrical ureas. Abstract : A highly efficient synthesis of unsymmetrical sulfoximine ureas has been developed. The reaction unites simple N H‐sulfoximines and acyl azides by a formal Curtius rearrangement as the key step. This reaction omits the generation of hazardous byproducts and could be easily scaled up to gram scale, thus allowing a practical and environmentally benign path for the synthesis of medicinally important sulfonimidoyl unsymmetrical ureas.